Flow Line of the Ice Sheet over Mizuho Plateau - Naruse, R.; Shimizu, H. (1978)
P(論文) Flow lines of the ice sheet surface in Mizuho Plateau, East Antarctica were deduced from the results of observations of topographic features of the surface and measurements of surface flow of the ice sheet. This paper gives the distribution of paths of ice flow over Mizuho Plateau, and also the results of surface strains of the ice sheet measured by the square strain grids. Tensile strains whose directions were roughly parallel to the directions of the ice flow were predominant almost all over Mizuho Plateau. Considerably large compressive strains were observed in such regions with remarkable surface depressions as Mizuho Camp. The ice mass of 4.5×(10)^9 ton a year was estimated to pass across the vertical cross section along Route A (from A033 to S240), while 3×(10)^9 ton a year across Route S (from S124 to S240), both towards the Shirase Glacier. departmental bulletin paper